1969
DOI: 10.1103/physrevlett.23.930
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy InelasticepScattering at 6° and 10°

Abstract: carbon data, R = (1.042 ±0.020) -[1.04 ±0.91 (GeV/c 2 )~4]Q w 4 ,giving A + = <*> and A_ = 0.99 GeV/c 2 ; and A + > 1.06 and A_ >0.77 GeV/c 2 at the 95% confidence level.In conclusion, the results of this experiment are in agreement with the predictions of quantum electrodynamics as described by Bjorken, Drell, and Frautschi for the photoproduction of electron pairs.We would like to thank M. D. Rousseau for his invaluable contribution in the early stages of the experiment, and M. W. Collins and A. E. Groome fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
354
1
7

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(369 citation statements)
references
References 21 publications
7
354
1
7
Order By: Relevance
“…Since the discovery of Bjorken scaling [1] and its violation [2] at fixed target experiments, much progress has been made in extending the kinematic range of measurements in terms of the Bjorken variable x and the modulus of four-momentum transfer squared Q 2 . The H1 and ZEUS experiments at the HERA ep collider have shown that the Q 2 evolution of the proton structure function F 2 (x, Q 2 ) is well described by perturbative QCD (pQCD) throughout a wide range in x and Q 2 [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of Bjorken scaling [1] and its violation [2] at fixed target experiments, much progress has been made in extending the kinematic range of measurements in terms of the Bjorken variable x and the modulus of four-momentum transfer squared Q 2 . The H1 and ZEUS experiments at the HERA ep collider have shown that the Q 2 evolution of the proton structure function F 2 (x, Q 2 ) is well described by perturbative QCD (pQCD) throughout a wide range in x and Q 2 [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These were verified by experiments at SLAC in 1969 and provided strong evidence for a particle interpretation of quarks [56,57].…”
Section: Brief History Of Quantum Chromodynamicsmentioning
confidence: 58%
“…Mas, em 1969 no SLAC foi feita uma descoberta inesperada. Estudos de processos de espalhamento inelástico profundo (grande momento transferido) como e − -p, e − -dêuteron (queé o núcleo do deutério, ou hidrogênio pesado, e está formado por um próton e um nêutron) e múons em prótons e dêuteron, foi observado um comportamento diferente do esperado, nas seções de choque chamado de scaling [73][74][75] (usaremos aqui a palavra em inglês [76], constituintes pontuais, dentro dos núcleons. Estes pártons seriam em um número arbitrariamente grande segundo Feynman.…”
Section: Os Experimentos Da Colaboração Gargamelleunclassified